Penghijauan di Areal Akademi Komunitas Olat Maras Kabupaten Sumbawa: Greening in the Olat Maras Community Academy Area, Sumbawa Regency - Musmulyadin Musmulyadin; Armansyah; Iman Irwansyah; Pipit Puspitasari; Ofah Syarofatunnisah; Samsuddin Samsuddin; Nova Novriani; Berri Sailendra (Experimental Student Experiences, 2022)
Community service in the Olat Maras Community Academy area is carried out in the form of greening activities to restore the natural environment of Pernek Village, Moyo Hulu District, Sumbawa Regency which was originally barren and arid. The environment in this region is very arid and often experiences flooding every time it rains. This community service activity was carried out for two months from November to December 2022. The reforestation activity was in the form of replanting trees on empty land around the higher education area of the Olat Maras Community Academy. The target of this service activity is the preservation of the area or vacant land around the Olat Maras Community Academy area which is in the area of Pernek Village, Moyo Hulu District, Sumbawa Regency. The purpose of carrying out this community service activity is to restore the function of vacant land or land, namely to hold water during the rainy season and make the environment beautiful during the dry season. As many as 200 tree seeds were successfully planted so that the Olat Maras Community Academy area in the Pernek area, Moyo Hulu District, Sumbawa Regency could return to being green and beautiful.